2020
DOI: 10.1016/j.jallcom.2019.153078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermo-mechanical processing on structure and mechanical properties of a new metastable β Ti–29Nb–2Mo–6Zr alloy with low Young’s modulus

Abstract: A low Young's modulus is required for titanium alloys used in orthopedic implants, such as hip prosthetic stems, in order to avoid stress shielding due to a large difference in Young's modulus between the prosthetic stem and the cortical bone. The low Young's modulus has been observed to occur in metastable b-Ti alloys by precipitation of a stress-induced a 00 martensite during cold deformation. Under this context, the Influence of thermo-mechanical processing on the microstructure and mechanical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 23 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, an implant with a low elastic modulus can avoid the stress shielding effect [2,3]. The yield strength/modulus (σ y /E)(× 1000) ratios and moduli of Ti-25Nb-8Sn under various TMT conditions and various β-type Ti alloys [1,9,12,28,37] are shown in Fig. 5 and Table 3.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an implant with a low elastic modulus can avoid the stress shielding effect [2,3]. The yield strength/modulus (σ y /E)(× 1000) ratios and moduli of Ti-25Nb-8Sn under various TMT conditions and various β-type Ti alloys [1,9,12,28,37] are shown in Fig. 5 and Table 3.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…As the grain size decreases, the elastic modulus of the alloy decreases significantly from 65 to 43 GPa, and the hardness of the alloy increases from 260 to 320 HV. Nunes et al [28] reported that with the percentage of cold rolling up to 90 %, the hardness of Ti-29Nb--2Mo-6Zr increased from 228 to 278 HV, and its elastic modulus decreased from 93 GPa to 76 GPa. Also, they found that a greater amount of α phase in Ti-29Nb--2Mo-6Zr was induced with increasing cold-rolling percentage.…”
Section: Introductionmentioning
confidence: 99%
“…A single β-phase state with a favorable {001} β <110> β crystallographic texture provides the highest recovery strains in these alloys [8,11,12]. The most effective tool to control the structural characteristics of these alloys is thermomechanical treatment (TMT) [10][11][12][13][14][15][16][17]. In a number of works [12,17], TMT combining hot/cold rotary forging and post-deformation annealing (PDA), was applied to Ti- (18)(19)Zr- (14)(15)Nb SMAs with the objective of forming a long-length bar stock 3-8 mm in diameter for bone-implant fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The structure, phase composition, texture, and consequently, the mechanical and functional properties of SMAs are commonly controlled by thermomechanical treatments (TMT) [6]. Combining the radial shear rolling (RSR) and rotary forging (RF) processes allows the formation of a favorable phase composition, structure and texture in semi-finished SMA products [7,8].…”
Section: Introductionmentioning
confidence: 99%